Effect of geometry and hybrid adhesive on strength of finger joints of Pinus elliottii subject to humidity and temperature - Messmer, Nigel R.; Anjos, Erick G. R.; Guerrini, Lilia M.; Oliveira, Maurício P. (The Journal of adhesion, 2018)
The optimized bonding of glued finger joints is required for structural and nonstructural applications. The use of nonspecific adhesives, combined with the joint geometry and exposure of joints to humidity and temperature, are factors that can compromise the durability of glued joints. The main objective of this study is the development of cross-linking poly(vinyl acetate) (PVAc) hybrid adhesive to produce nonstructural finger joints of Pinus elliottii with finger lengths of 6.5 and 4.5 mm. The adhesives were produced by emulsion copolymerization of vinyl acetate with n-butyl acrylate with different amounts of N-methylol acrylamide and blended with resorcinol-formaldehyde resin (RF) and aluminum chloride (AlCl 3 ). The rheological behavior of adhesives was investigated. We found that the joint configuration and the exposition time employed influenced joint strength. The PVAc/RF adhesive showed a thicker bond line and consequent deeper penetration into the pores of the wood as verified by microscopy analysis. Statistically differences in bond strength of the adhesive joints were found with respect to different conditioning times and finger length. The highest values were exhibited by the joints produced with a finger length of 6.5 mm and glued with the hybrid adhesive (AD-4) than that joints produced with a finger length of 4.5 mm.